EUROPEAN GROUND SQUIRREL (MAMMALIA: RODENTIA) POPULATION FROM EASTERN ROMANIA: DENSITY, DISTRIBUTION AND THREATS - Baltag, Emanuel Ştefan; Zaharia, Gheorghe; Fasolă, Lucian; Ion, Constantin (European Scientific Journal, ESJ, 2014)
The number of European Ground Squirrel (Spermophilus citellus) is in continuous decline across the species range, particularly in the southern, north-western and northern areas where decline is more severe. The species population from Eastern Europe is poorly studied and the main ecological indicators (density, distribution, trend and threats) are unknown. These data are very important for the species conservation strategy focused on actual information. During 2013 we conducted 600 transects in Eastern Romania for European Ground Squirrel counting. The density varies along the study area between 0 individuals/ha and 107 individuals/ha (with an average of 15.41 individuals/ha). Also, the species population from this area is highly fragmented with more colonies in the southern and eastern part of our study area. The main threats are habitat fragmentation, grazing management and floods. The protection of this species is poor, because Natura 2000 and national protection sites cover only small parts of the European Ground Squirrel colonies, most of them being in the state or private grazing areas. These are the first ecological indicators on European Ground Squirrel from Romania. All this information will contribute to Natura 2000 sites management and development, but also for the first national action plan for this species.